Cleanup chlorinated ethene-polluted groundwater using an innovative immobilized Clostridium butyricum column scheme: A pilot-scale study. (1st June 2022) - Lo, Kai-Hung; Lu, Che-Wei; Chien, Chih-Ching; Sheu, Yi-Tern; Lin, Wei-Han; Chen, Ssu-Ching; Kao, Chih-Ming
Abstract: In this study, the developed innovative immobilized Clostridium butyricum (ICB) (hydrogen-producing bacteria) column scheme was applied to cleanup chlorinated-ethene [mainly cis- 1, 2-dichloroethene ( cis- DCE)] polluted groundwater in situ via the anaerobic reductive dechlorinating processes. The objectives were to assess the effectiveness of the field application of ICB scheme on the cleanup of cis- DCE polluted groundwater, and characterize changes of microbial communities after ICB application. Three remediation wells and two monitor wells were installed within the cis- DCE plume. In the remediation well, a 1.2-m PVC column (radius = 2.5 cm) (filled with ICB beads) and 20 L of slow polycolloid-releasing substrate (SPRS) were supplied for hydrogen production enhancement and primary carbon supply, respectively. Groundwater samples from remediation and monitor wells were analyzed periodically for cis- DCE and its degradation byproducts, microbial diversity, reductive dehalogenase, and geochemical indicators. Results reveal that cis- DCE was significantly decreased within the ICB and SPRS influence zone. In a remediation well with ICB injection, approximately 98.4% of cis- DCE removal (initial concentration = 1.46 mg/L) was observed with the production of ethene (end-product of cis- DCE dechlorination) after 56 days of system operation. Up to 0.72 mg/L of hydrogen was observed in remediation wells after 14 days of ICB and SPRS introduction, which corresponded with the increased population of Dehalococcoides spp. ( Dhc ) (increased from 3.76 × 10 3 to 5.08 × 10 5 gene copies/L). Results of metagenomics analyses show that the SPRS and ICB introduction caused significant impacts on the bacterial communities, and increased Bacteroides, Citrobacter, and Desulfovibrio populations were observed, which had significant contributions to the reductive dechlorination of cis- DCE. Application of ICB could effectively result in increased populations of Dhc and RDase genes, which corresponded with improved dechlorination of cis- DCE and vinyl chloride. Introduction of ICB and SPRS could be applied as a potential in situ remedial option to enhance anaerobic dechlorination efficiencies of chlorinated ethenes. Graphical abstract: Schematic diagram showing the application of immobilized Clostridium butyricum system for the enhancement of chlorinated ethene dechlorination. Image 1 Highlights: Immobilized Cloristridium butyricum (ICB) can enhance DCE dechlorination. ICB can enhance H2 production and increase in microbial community. H2 production causes a significant growth of Dehalococcoides and RDase genes. Bacteroides, Citrobacter, and Desulfovibrio play key roles in DCE dechlorination.